Study on the Joint Toxicity of BPZ, BPS, BPC and BPF to Zebrafish - Ying Han; Yumeng Fei; Mingxin Wang; Yingang Xue; Hui Chen; Yuxuan Liu (Molecules, 2021)
Bisphenol Z (BPZ), bisphenol S (BPS), bisphenol C (BPC), and bisphenol F (BPF) had been widely used as alternatives to bisphenol A (BPA), but the toxicity data of these bisphenol analogues were very limited. In this study, the joint toxicity of BPZ, BPS, BPC, and BPF to zebrafish (Danio rerio) was investigated. The median half lethal concentrations (LC50) of BPZ, BPS, BPC, and BPF to zebrafish for 96 h were 6.9 × 105 µM, 3.9 × 107 µM, 7.1 × 105 µM, and1.6 × 106 µM, respectively. The joint toxicity effect of BPF–BPC (7.7 × 105–3.4 × 105µM) and BPZ–BPC (3.4 × 105–3.5 × 105µM) with the same toxic ratio showed a synergistic effect, which may be attributed to enzyme inhibition or induction theory. While the toxicity effect of the other two bisphenol analogue combined groups and multi-joint pairs showed an antagonistic effect due to the competition site, other causes need to be further explored. Meanwhile, the expression levels of the estrogen receptor genes (ERα, ERβ1) and antioxidant enzyme genes (SOD, CAT, GPX) were analyzed using a quantitative real-time polymerase chain reaction in zebrafish exposure to LC50 of BPZ, BPS, BPC, and BPF collected at 24, 48, 72, and 96 h. Relative expression of CAT, GPX, and ERβ1 mRNA declined significantly compared to the blank control, which might be a major cause of oxidant injury of antioxidant systems and the disruption of the endocrine systems in zebrafish.